Origin and age of carbon in the cellulose of mid-latitude tree rings - Kromer, Bernd; Wacker, Lukas; Friedrich, Michael; Lindauer, Susanne; Friedrich, Ronny; Bitterlich, Julian; Treydte, Kerstin; Fonti, Patrick; Martínez-Sancho, Elisabet; Nievergelt, Daniel (Radiocarbon, 2024)
Cellulose of tree rings is often assumed to be predominantly formed by direct assimilation of CO2 by photosynthesis and consequently can be used to reconstruct past atmospheric 14C concentrations at annual resolution. Yet little is known about the extent and the age of stored carbon from previous years used in addition to the direct assimilation in tree rings. Here, we studied 14C in earlywood and latewood cellulose of four different species (oak, pine, larch and spruce), which are commonly used for radiocarbon calibration and dating. These trees were still growing during the radiocarbon bomb peak period (1958-1972). We compared cellulose 14C measured in tree-ring subdivisions with the atmospheric 14C corresponding to the time of ring formation. We observed that cellulose 14C carried up to about 50% of the atmospheric 14C signal from the previous 1-2 years only in the earlywood of oak, whereas in conifers it was up to 20% in the earlywood and in the case of spruce also in the latewood. The bias in using the full ring of trees growing in a temperate oceanic climate to estimate atmospheric 14C concentration might be minimal considering that earlywood has a low mass contribution and that the variability in atmospheric 14C over a few years is usually less than 3‰.